Approaches to Salivary Cortisol Collection and Analysis in Infants. (October 2014) - Tryphonopoulos, Panagiota D.; Letourneau, Nicole; Azar, Rima
Salivary cortisol is becoming more commonly utilized as a biologic marker of stress in observational studies and intervention research. However, its use with infants (12 months of age or younger) is less widespread and poses some special challenges to researchers. In order to decide on the most suitable collection procedure for salivary cortisol in infants, a number of criteria should be considered. This article will aid investigators interested in integrating salivary cortisol measurement into their research studies by presenting (1) an overview of the patterns of cortisol secretion in infancy including the development of diurnal rhythm and response to stress; (2) a comparison of the most commonly used approaches for collecting salivary cortisol samples in infants including cotton rope, syringe aspiration technique, filter paper, hydrocellulose microsponge, and the Salimetrics children's swab; (3) a discussion of the factors contributing to heightened cortisol variability in infancy and how these can be limited; (4) analytical issues associated with cortisol measurement; and (5) examples of criteria to consider when choosing a saliva sampling method and lab for conducting assays.